Contraceptive Practice and Protection of Womens Health (Bangladesh Medical Journal, 2010)
Family planning is an essential tool for reducing fertility rate. An increase in contraceptive prevalence results in reduction of population growth, which in turn contributes significantly to the improvement of maternal health. It is a cross-sectional study done during period of April-July 2007 in a large Medical Centre at Motijheel, Dhaka. Information on reproductive history was obtained to find out their contraceptive prevalence and regulation of fertility. Two hundred and thirty one (231) women (childbearing age) were selected randomly to find out their contraceptive prevalence. Eighty four (n=197) percent women needs family planning service .Among them 87.82 percent (N-173) use any method of contraception. 79.76% ( N-138) women use modern method and 20.23 percent ( N-35) couple use natural method .Thirty three (33.53 %)percent couple practice barrier method, twenty two (22.54%) percent use oral pill. Present study revealed that contraceptive practice and fertility rate both are low among servicing women. Contraception and fertility control is an underlying factor for the achievement of several Millennium Development Goals (MDGs). For reduction of infant mortality (4th MDG) and maternal mortality (5th MDG) contraception is essential. Finally it plays a role in combating poverty within the first MDG. DOI: 10.3329/bmj.v39i1.6227 Bangladesh Medical Journal 2010; 39(1): 11-15